PENGARUH ROTASI AUDIT, AUDIT TENURE DAN REPUTASI AUDIT TERHADAP AUDIT REPORT LAG DENGAN KOMITE AUDIT SEBAGAI PEMODERASI - Selvi Sesariani; Tomi Riyadi (Publika Citra Media, 2026)
This study aims to examine and analyze the effect of audit rotation, audit tenure, and audit reputation on audit report lag with the audit committee as a moderating variable. This research is quantitative with an associative approach. The population consists of all property and real estate companies listed on the Indonesia Stock Exchange in 2020–2024. The sampling method used is purposive sampling. The data analysis techniques employed include model estimation tests, model tests, data quality tests, and hypothesis testing using multiple linear regression analysis with EViews 12 software. The results of this study indicate that audit rotation and audit reputation have no effect on audit report lag, while audit tenure has an effect on audit report lag. Simultaneously, audit rotation, audit tenure, and audit reputation influence audit report lag. Furthermore, the audit committee variable is not able to moderate the influence of audit rotation, audit tenure, and audit reputation on audit report lag.